Social Protection Situational Analysis : North Macedonia - World Bank (Washington, DC, 2022)
North Macedonia has strengthened its social protection system through comprehensive reforms in social assistance, social services, and pensions. This note considers, based on existing evidence, the extent to which the social protection system in North Macedonia satisfies four basic principles: adequacy; balance and effectiveness; equity; and sustainability. The situational analysis note is structured as follows: section two reviews the main poverty and labor market outcomes in North Macedonia, comparing it with peers and relevant country groups. Section 3 introduces a framework to consider the performance of the social protection system and then outlines the broad characteristics of social protection in North Macedonia, by program type and expenditure. Section 4 looks at non-contributory cash transfers to support the poor, the vulnerable and persons with disabilities and assesses the recent social assistance reform. Section 5 discusses social services and assesses the changes in social services as a result of the social protection reform as well as the introduction of case management, which aims to help ensure the provision of integrated services to the poor and vulnerable. Section 6 discusses pensions. Section 7 explores employment and active labor market programs (ALMPs). Section 8 considers the recent social protection response to the Coronavirus disease 2019 (COVID-19) pandemic and section 9 concludes by offering an assessment of the main areas for reform.